English words and phrases in Croatian - Perić, Marija (ELOPE (Ljubljana), 2015)
The focus of this paper is on language attitudes towards English words and phrases in the Croatian language. In order to prevent loanwords, linguistic purism has arisen as a theory about what languages should be like. The tradition of linguistic purism in Croatia has been shaped by various socio-historical factors. English may be viewed as a language of opportunity, or as a threat to the survival of other, usually minority and endangered, languages. In order to provide an insight into the use of English words and phrases in the Croatian context, a questionnaire about language attitudes and awareness was conducted on 534 participants. The aim of the questionnaire was to determine participants' language attitudes and familiarity with English words and phrases. The results show that although people in Croatia generally like English, many of them are not familiar with English words, especially older participants and those with little or no knowledge of the English language. Moreover, the results indicate that the younger generation is more inclined towards English than the older generation; however, they are not as familiar with Croatian equivalents as they claim.
Keywords: angleščina; Croatian; English; hrvaščina; izposojenke; jezikovni purizem; jezikovni stik; odnos